O programa Reinventando o Ensino Médio no estado de Minas Gerais: uma análise sobre as condições do trabalho docente - Erivane Rocha Ribeiro (2015)
The proposal of this research is to recognize aspects related to the teachers' working conditions in the Reinventing High School Program from the Education Secretary from the State of Minas Gerais. The program was initiated in 2012 and suspended in January 2015. The aim is describing and interpreting the changes in high school organization with the implementation of this program, that has initiated in 2012. Besides, investigating and analyzing the teachers' working conditions who has participated in the program at different stages in Belo Horizonte; as well as contextualizing and interpreting the conception of the research's subjects related to the program: directors, coordinators and teachers. In order to present the current high school situation in the country and in Minas Gerais, a survey of the educational statistics was done collecting: enrollments according to the administrative dependence, kind of course and general aspects on teachers. The hypotheses of the research were defined based on this approach on the object of study. Firstly, it is considered that the implementation of the Reinventing High School Program in the state of Minas Gerais assumes a high school valuation process, in which redefines part of the curriculum and creates organized specific disciplines in "employability areas". Secondly, the program contributes to the improvement of the teachers' working conditions. Finally, the program provides a greater interaction among teachers contributing to the collective work, at the same time, leading to an intensification of the teachers' work. The sources of the research from the two schools sampled were the legislation concerning national and state levels (laws, decrees, regulations and judgements/ resolutions), documents and studies done by the Education Secretary from the state of Minas Gerais and the Single Union of Education Workers of Minas Gerais, added to the semi-structured interviews with state leaders, as well as with head teachers and teachers in designated areas of employability. The data and the analysis about the Reinventing High School Program and the teachers' working conditions present as a result a critical view of teachers as well as of some respondents to the Program, particularly considering the increased workload, perceived as a work intensification without formal recognition measured in the relation between adequate remuneration to the working period. It is also evident an efficient vision-based of the Program by some of the interviewees. On the other hand, it is perceived the high school valuation, the improvement of teachers' working conditions due to the availability of the technological resources and, in the end, the need for investment in training teachers to develop in the areas of employability.